“Poetry whirlpool”: Rhythm and Tangible Language in the Works of the Wu-Tang Clan and Booba - Léopold Reigner (Itinéraires)
Rap is an art form centered around language. As such, it may be studied using a language-focused methodology. However, in the case of rap, the delivery is almost always performed by the artist themselves, so that rap is always performed literature, and an analysis should take this performance into account. This raises the issue of the validity of performing close readings on works which exist primarily in oral rather than in written form. Studies of orality and public readings of poetry have put forth the notion of close listening, which unlike close reading encompasses the analysis of the oral delivery of a written text. A study of rap based on close listening, examining transcripts while taking the delivery into account, may prove revealing as to the changes in meaning involved in the performance. The lyrics and performances of a rap group, the Wu-Tang Clan, containing a diversity of styles, even genres, along with a non-US based solo rapper, Booba, separated by time, geography and style but linked by a common uncompromising misclassification in the thug rap genre as well as a complex approach to the lyrical warfare trope, could constitute diversified objects of study leading to general observations on these artists and their works.